A pilot geomagnetic and magnetotelluric survey in Mogod area of the Eastern Hangai, Mongolia - E, Batmagnai; B, Tsegmed; T, Nasan-Ochir; S, Gantsogt; B, Eldew-Ochir (Proceedings of the Mongolian Academy of Sciences, 2019)
The paper are the preliminary results of the study of the hydrothermal system of Khulj, which is located in Mogod soum of Bulgan aimag, carried out using magnetotelluric and magnetic methods. Khulj’s hydrothermal system is an interesting geodynamic structure located in the area of a young volcanic mountain in the eastern part of the Khangai Mountains. The study was carried out using two geophysical methods. The first is the magnetotelluric measurement, which registered variations of 3 components of magnetic field (Bx, By, Bz), and 2 components of electric field (Ex, Ey). In addition, we have provided a total of 8 magnetic field profiles for an area of ​​4 x 8 km. The sample rate of the total magnetic field was 3 seconds, which corresponds to about 3 meters. The programme’s codes are written in C ++ and Matlab and the result of this code is a programme called INV2DMAG. This programme is based on the inversion method of the Levenberq-Marquardt algorithm. Magnetotelluric results show that one-dimensional models clearly display the depth, the thickness of precipitation, as well as the thickness of the Moho boundaries. A preliminary two-dimensional magnetic structure, determined from small-length profiles, provides very useful insight into understanding the shallow deep structure of the sedimentary soil of the region in and around Mogod. In the Mogod’s hydrothermal system, we expect that the hot fluid heats up from granites, which have a deep source. For a detailed research, repeat field measurement is required to determine not only the structure of this geothermal system but also to determine the depth of the sedimentary soil.